Uncovering Comedy: Explorations of Humor in 19th Century American Literature. - Jani, Henry A. (Tufts Archival Research Center, 2018)
In closely considering the role of humor across Moby-Dick, Ruth Hall, and The Last of the Mohicans, we can bring light to the fact that 19th c. American novels reveal the power, but also imprecision, of comedy as a political tool. Each author purposefully crafted their brand of humor to elicit a certain response from the reader, while also interjecting their opinion on a certain social, cultural or economic reality.